(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article examines the main physical and mechanical properties of a child safety device in passenger cars, as well as the classification, design features and the degree of relevance of its installation. And the level of quality of the device is determined, as well as its safety for human life.